Game based learning as a strategy to increase intrinsic motivation in learning cost and management accounting / Rafizan Abdul Razak … [et al.] - Abdul Razak, Rafizan; Kasim, Eley Suzana; Daud, Dalila; Dol@ Abdul Wahid, Akma Hidayu (Faculty of Accountancy, 2019)
Academicians play a crucial role in students’ empowerment and enthusiasm for learning to achieve better grades in their studies. The existence of various modes of learning such as e-learning, on-line games, blended learning and group project allow students to engage in their learning process. However, despite these alternatives, little benefit is expected if students are not motivated to learn their subject matters. Therefore, the objective of this paper is to investigate the effect of intrinsic motivation among students in learning cost and management accounting course via education games. Two games known as “Smart Costing Game” and D’Bees Game for Fun” had been developed to help students in learning basic cost classification during cost and management accounting course. The data were gathered using an online survey based on intrinsic motivation inventory and analyses were done using descriptive statistic. Results demonstrated that a majority of students agreed that the games were found to be able to increase their interest, providing useful and effective learning activity, motivating and engaging in learning the course. These games also enabled students to develop their soft skills, problem solving and analytical skills at the early year of their learning experience at universities. Given the general critics of cost and accounting educators who were always textbook oriented, these findings have significant implication to increase the intrinsic motivation among students in learning accounting courses.